Review on the Current Trends of Toxoplasmosis Serodiagnosis in Humans - Ybañez, Rochelle Haidee D.; Ybañez, Adrian P.; Nishikawa, Yoshifumi (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasmosis is a widely distributed zoonotic infection caused by the obligate intracellular apicomplexan parasite Toxoplasma gondii. It is mainly transmitted through the ingestion of oocysts shed by an infected cat acting as its definitive host. The key to effective control and treatment of toxoplasmosis is prompt and accurate detection of T. gondii infection. Several laboratory diagnostic methods have been established, including the most commonly used serological assays such as the dye test (DT), direct or modified agglutination test (DAT/MAT), indirect haemagglutination test (IHA), latex agglutination test (LAT), indirect immunofluorescent test (IFAT), enzyme-linked immunosorbent assays (ELISA), immunochromatographic tests (ICT), and the western blot. Nonetheless, creating specific and reliable approaches for serodiagnosis of T. gondii infection, and differentiating between acute and chronic phases of infection remains a challenge. This review provides information on the current trends in the serodiagnosis of human toxoplasmosis. It highlights the advantages of the use of recombinant proteins for serological testing and provides insight into the possible future direction of these methods.